Interest, politics and drift in policy implementation: the case of trafficking prevention measures in Brazil - Hofmann, Susanne (2021)
This article scrutinizes the anti-trafficking efforts that the PT Government in Brazil undertook to implement the National Anti-Trafficking Policy in collaboration with different civil society organizations. Focusing on crime prevention measures, the article analyses the perceptions and understandings of trafficking, and the values and norms implicit in those, as well as the relationships developed between pubic officials and members of the civil society in this context. Examining everyday policy work, the article illustrates that policy implementation cannot be considered a mere technical-rational endeavor, in which replaceable officials deliver consistent and replicable outcomes based on unambiguous rules, assigned roles, and specified tasks and procedures. On the one hand, personality, personal motives and interests played a significant role in forging policy implementation focus and approach. On the other hand, the public officials struggled with the activists’ attempts to shift policy concerns and implementation into a direction that diverged from their own politics